Synergy of Inorganic Fillers in Composite Thermoplastic Polymer/Ionic Liquid/LiTFSI Electrolytes. Issue 7 (6th February 2020) - González, F.; Garcia-Calvo, O.; Tiemblo, P.; García, N.; Fedeli, E.; Thieu, T.; Urdampilleta, I.; Kvasha, A.
Abstract : The development of novel solid electrolytes, which can be processed using solvent-free methods, is one of the keys for successful industrialization of solid state batteries and their further implementation in electrical vehicles. Here, we study thermoplastic solid state electrolytes based on polyethylene oxide (PEO), 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR14 TFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and two inorganic fillers with different morphology and nature (modified sepiolite (TPGS-S) and garnet-type Li7 La3 Zr1.75 Nb0.25 O12 (LLZNO) prepared by solvent free extrusion method. Several thermoplastic polymer electrolytes (TPEs) are prepared and comprehensively studied. Composite thermoplastic electrolyte TPE-S10G10 containing 10 wt% of TPGS-S and 10 wt% of LLZNO fillers shows the best electrochemical performance in Li-LiFePO4 solid state batteries operating under 0.2C/0.5D cycling conditions at 60 °C. Solid state cell with TPE-S10G10 electrolyte retains 80% of initial discharge capacity after 540 cycles. Thus, a synergetic effect of using two different fillers, which can be exploited during the development of TPEs, is clearly demonstrated.